ABL CER Learning Improves Basic Physics Conceptual Understanding: Pembelajaran ABL CER Meningkatkan Pemahaman Konsep Fisika Dasar - Yusal, Yulianti; Sangkala, Nur Rahmah; Alqadri, Zulqifli; Syakur, Akhmad; Daud, Dalla Haji (Pedagogia : Jurnal Pendidikan, 2026)
General Background: Higher education requires students to master conceptual knowledge alongside scientific reasoning through structured argumentation involving claims, evidence, and reasoning. Specific Background: However, students’ conceptual understanding in basic physics often remains weak due to unstructured learning practices that fail to reveal reasoning processes and support evidence-based explanations. Knowledge Gap: Although argumentation-based learning is recognized in science education, its structured implementation using Claim-Evidence-Reasoning (ABL-CER) in higher education physics contexts remains insufficiently examined. Aims: This study aims to determine the effect of ABL-CER on students’ conceptual understanding in Basic Physics. Results: Using a quasi-experimental posttest-only control group design with 71 students, the experimental group achieved a higher mean score (72.43) than the control group (64.50), with a significant difference (Sig. 0.001 < 0.05). Novelty: This study demonstrates that structured argumentation through CER explicitly supports conceptual reasoning by requiring students to formulate claims, select relevant evidence, and connect them through scientific reasoning. Implications: The findings suggest that ABL-CER provides a systematic and assessable framework for strengthening conceptual understanding, particularly in physics topics prone to misconceptions, and supports its application in higher education and teacher preparation contexts. Highlights • Experimental class achieved higher posttest scores than comparison group• Structured reasoning process supports deeper conceptual processing• Argumentation activities facilitate evaluation and revision of ideas KeywordsArgumentation-Based Learning; Claim Evidence Reasoning; Conceptual Understanding; Basic Physics; Higher Education